Remembering 1759 : The Conquest of Canada in Historical Memory - Reid, John G., 1948-; Buckner, Phillip A. (Phillip Alfred), 1942- (Book collections on Project MUSE., 2012)
Combined with Revisiting 1759, this collection provides readers with the most comprehensive, wide-ranging assessment to date of the lasting effects of the Conquest of Canada.